The Spanish holocaust : inquisition and extermination in twentieth-century Spain - Preston, Paul 1946- (W. W. Norton & Company, 2012)
Long neglected by European historians, the unspeakable atrocities of Franco's Spain are finally brought to tragic light in this definitive work by Paul Preston, the world's foremost historian of 20th-century Spain